Herança e subversão: a verdade na relação êxtima entre psicanálise e ciência - Figueiredo, Ingrid Porto de (2018)
This thesis aimed to address the notion of truth in the relationship of internal exclusion among psychoanalysis and science, in order to establish the limits between these fields. Our approach is to reach the articulation amongst truth, knowledge, and enjoyment as delimited by logic and poetic interpretation. We start from the tension imposed by the paraconsistent place of psychoanalysis as an inherited and subversive paradigm of the field of science, seeing that it emerges in the scientific context of the late nineteenth century, since it appears from the problem-solving activities, typical of a normal science, undertaken by Freud in his investigation of psychic facts. The Austrian psychoanalyst invented a totally unprecedented method, the interpretation, which sought to decipher the truth of the unconscious, which was raised to the status of concept. With this method, he was able to approach the so-called formations of the unconscious – the symptom, the dream, the jokes and the Freudian slip – from the free association and the transferential management. But it was with Lacan that psychoanalysis shifted the unconscious that tells the truth to the truth that speaks for itself. In his teaching, the truth was placed as a material cause, unlike science, different field that have truth as a formal cause. In addition, the place of the cause is situated regarding the subject – the subject of science, created and forecluded by the scientific field – in its articulation with the materiality of the signifier, with the object a and the field of enjoyment, which is baptized as the Lacanian field, since it was inaugurated from the advances of Lacan in relation to the Freudian drive theory. Thereafter, the unconscious structured as a language advances to the unconscious in its real strand, bringing the logical enterprise to demonstrate the inconsistency of the Other and the impossibility of the universe of the discourse. Moreover, with the theory of the four discourses Lacan was able to delimit the relationship between knowledge, truth and enjoyment, where knowledge presents itself as a medium of enjoyment, and truth as fraternal to the enjoyment, where the psychoanalyst identifies the barrier of castration as that which imposes a disjunction between knowledge and truth. From this theorization, Lacan advances to the formulas of sexuation, in order to locate the S(). In these formulas, Lacan placed the phallic enjoyment, the not-all phallic enjoyment, in order to demonstrate the possibility of transmission of the impossible at the end of analysis, where truth appears in its not-whole slope, since the more truth speaks, the more it camouflages itself. The aphorism "I, the truth, speak" points to a truth that speaks, without saying the very own truth and the truthful about the truthful. This impossibility lies in the fact that there is no metalanguage, and that "what one might be saying remains forgotten behind what is said in what is heard", that is, the "what is said" is extracted of the course of an analysis, which is the construction of fantasy itself – a saying that addresses the truth of fantasy. The proposal of the Lacanian operation via the poetic interpretation through the use of the poetic function of language aims the sense and goes against the phallic signification. For that reason, he resorted to Chinese poetic writing and to the blow of the median emptiness, for making something else resound. It is a question of circumscribing a truth that is poetic and not-whole, taken from the tension between sound and sense, in the articulation between the matheme and the poem